2015
DOI: 10.1080/21645515.2015.1056952
|View full text |Cite
|
Sign up to set email alerts
|

RecombinantLactobacillus plantaruminduces immune responses to cancer testis antigen NY-ESO-1 and maturation of dendritic cells

Abstract: Given their safe use in humans and inherent adjuvanticity, Lactic Acid Bacteria may offer several advantages over other mucosal delivery strategies for cancer vaccines. The objective of this study is to evaluate the immune responses in mice after oral immunization with Lactobacillus (L) plantarum WCFS1 expressing a cell-wall anchored tumor antigen NY-ESO-1. And to investigate the immunostimulatory potency of this new candidate vaccine on human dendritic cells (DCs). L. plantarum displaying NY-ESO-1 induced NY-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…26 Furthermore, this strain exhibits natural immuno-adjuanticity and more immunogenicity than L. lactis and L. casei and modulation of immune system toward Th1 responses. 2,5,[28][29][30] On the other hand, LLO facilitates the stimulation of both the CD4+ T cell through MHC class II and CD8+ T cell through MHC class I antigen presentation. 31,32 It is mentioned that nanomer LLO 91-99, is an immunodominant epitope that induces both cell-mediated and humoral immunities.…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, this strain exhibits natural immuno-adjuanticity and more immunogenicity than L. lactis and L. casei and modulation of immune system toward Th1 responses. 2,5,[28][29][30] On the other hand, LLO facilitates the stimulation of both the CD4+ T cell through MHC class II and CD8+ T cell through MHC class I antigen presentation. 31,32 It is mentioned that nanomer LLO 91-99, is an immunodominant epitope that induces both cell-mediated and humoral immunities.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation found that DC immunity in NPC patients was augmented by FSTL1. Similarly, TNF‐α has been shown to promote the development of immature DCs into mature DCs . Therefore, the mechanism by which FSTL1 expedites the immune ability of DCs should be elucidated from this perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TNF-α has been shown to promote the development of immature DCs into mature DCs. 54,55 Therefore, the mechanism by which FSTL1 expedites the immune ability of DCs should be elucidated from this perspective. Above all, it is important to investigate the mechanism by which FSTL1 affects DCs to provide a basis for new antitumor immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal lipoprotein anchor used in this study has previously been used for functional display of invasin from Yersinia pseudotuberculosis (37) and a CCL3 chemokine (39), whereas the C-terminal cell wall anchor has been exploited for functional display of cancer antigens (34,44) and an anti-DEC-205 antibody (40).…”
Section: Discussionmentioning
confidence: 99%